Molecular Mechanisms of REM Sleep - Yamada, Rikuhiro G.; Ueda, Hiroki R. (Frontiers in Neuroscience, 2020)
The REM sleep is a paradoxical sleep state characterized by brain activity similar to wakefulness, rapid-eye-movement, and lack of muscle tone. REM sleep is a fundamental brain function as it is evolutionary conserved across species, including human, mouse, bird, and even reptiles. The physiological importance of REM sleep is highlighted by severe sleep disorders incurred by a failure in REM sleep regulation. Despite the intense interest in the mechanism of the REM sleep regulation, the molecular machinery is largely left to be investigated. In models of REM sleep regulation, acetylcholine has been a pivotal component. However, even newly emerged techniques such as pharmacogenetics and optogenetics, have not fully clarified the function of acetylcholine either at the cellular level or neural-circuit level. Recently, we discovered that the Gq type muscarinic acetylcholine receptor genes; Chrm1 and Chrm3, are essential for REM sleep. In this review, we attempt to develop a perspective of current knowledge on REM sleep from a molecular viewpoint. This attempt should be a starting point to clarify the molecular machinery underlying the REM sleep regulation and will provide molecular insights to explore physiological functions of REM sleep and its pathological roles in REM-sleep-related disorders such as depression, PTSD, and neurodegenerative diseases.